2010
DOI: 10.1248/bpb.33.1043
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Stirring-Induced Microparticle Formation in Monoclonal Antibody Solutions

Abstract: Monoclonal antibodies are being widely used for the treatment of various diseases. Microparticle formation in high-concentration protein solutions is a major problem during the manufacture of therapeutic monoclonal antibodies, because aggregation leads to fouling of aseptic filters and may lead to an immunogenic reaction in patients. We found that stirring using a traditional bottom-magnetic type stirrer results in extensive and sustained formation of 500-nm diameter protein microparticles arising from shear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…Previously, we reported that the stirring-induced aggregation of antibodies can be prevented by replacing bottom-magnetic type stirrers with top-entering type stirrers. 18) And our preliminary experiments indicated that heat had the most significant effects on the aggregation and degradation of antibodies among heat, vibration, and freeze-thawing (not shown). So we analyzed the effects of heat which accelerates deterioration of antibodies during storage.…”
mentioning
confidence: 89%
“…Previously, we reported that the stirring-induced aggregation of antibodies can be prevented by replacing bottom-magnetic type stirrers with top-entering type stirrers. 18) And our preliminary experiments indicated that heat had the most significant effects on the aggregation and degradation of antibodies among heat, vibration, and freeze-thawing (not shown). So we analyzed the effects of heat which accelerates deterioration of antibodies during storage.…”
mentioning
confidence: 89%
“…Protein solutions are susceptible to particulate formation when mixed for extended times with bottom mounted mixers (Ishikawa and Kobayashi 2010). Homogeneity studies, air entrainment studies, and product impact development/characterization studies are required.…”
Section: Example Of Gap Analysis and Risk Assessmentmentioning
confidence: 99%
“…20) The mobile phase contained 20 mM sodium phosphate (pH 7.0) and 500 mM sodium chloride. The experimental conditions were as follows: injected protein, 20 mg; flow rate, 0.5 ml/min; detection wavelength, 215 nm; and analysis time, 30 min.…”
Section: Size-exclusion Chromatographymentioning
confidence: 99%
“…arated from dimers and trimers. 6,20) However, SEC is not applicable to the detection of much larger aggregates. The aggregates of anti-DNP antibodies were investigated by DLS measurements, which give information on the size distribution from monomers (10 nm) to large aggregates (1000 nm).…”
Section: Fig 4 Turbidity Decrease Of Anti-dinitrophenol (Dnp)1-di Smentioning
confidence: 99%